2020
DOI: 10.1051/0004-6361/202039114
|View full text |Cite
|
Sign up to set email alerts
|

Disc galaxy resolved in H I absorption against the radio lobe of 3C 433: Case study for future surveys

Abstract: The neutral atomic gas content of galaxies is usually studied in the H I 21 cm emission line of hydrogen. However, as we go to higher redshifts, owing to the weak strength of the transition, we need very deep integrations to detect H I emission. The H I absorption does not suffer from this dependence on distance as long as there is a sufficiently bright radio source to provide the background continuum. However, resolved H I absorption studies of galaxies are rare. We report one such rare study of resolved H I … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 88 publications
1
2
0
Order By: Relevance
“…This scenario was also suggested in the recent study of the Dragonfly Galaxy (MRC 0152-209) by Lebowitz et al (2023). The scenario where jet-cloud interactions convert jet power into radio luminosity also agrees with studies of mostly ionized and neutral gas around low-z radio sources (e.g., van Breugel et al 1985;Fosbury et al 1998;Villar-Martín et al 1999Tadhunter et al 2000;Morganti et al 2002Morganti et al , 2011Murthy et al 2020) and has been proposed to explain the relatively large fraction of young and compact radio sources seen among starbursting radio galaxies at low-z (Tadhunter et al 2011).…”
Section: Jet-cloud Interactions: Synchrotron Brighteningsupporting
confidence: 79%
“…This scenario was also suggested in the recent study of the Dragonfly Galaxy (MRC 0152-209) by Lebowitz et al (2023). The scenario where jet-cloud interactions convert jet power into radio luminosity also agrees with studies of mostly ionized and neutral gas around low-z radio sources (e.g., van Breugel et al 1985;Fosbury et al 1998;Villar-Martín et al 1999Tadhunter et al 2000;Morganti et al 2002Morganti et al , 2011Murthy et al 2020) and has been proposed to explain the relatively large fraction of young and compact radio sources seen among starbursting radio galaxies at low-z (Tadhunter et al 2011).…”
Section: Jet-cloud Interactions: Synchrotron Brighteningsupporting
confidence: 79%
“…Shock excitation has been found in several other objects presenting radio jets, such as M51 [60], Coma A [93], the Beetle galaxy [94], PKS B1934-63 [95], 3C 320 [96], 4C 31.04 [78], 3C 433 [97], J1220+3020 [98], Cygnus A [66], among others. Shock excitation has been found not only in the ionized gas phase, but also sometimes in molecular or neutral gas.…”
Section: Signatures Of Shocks Due To Radio Jetsmentioning
confidence: 97%
“…The few detections of H absorption against a radio lobe have been discovered serendipitously, similar to the case presented here, rather than from a comprehensive survey searching for absorption against extended radio sources. A recent study by Murthy et al (2020) reported H absorption against the radio lobe of 3C 433. In that case, the absorber is a faint disc galaxy with stellar mass of ∼ 10 10 𝑀 blueshifted by only ∼ 50km s −1 from the systemic velocity of the host galaxy, but has a similar line width of ∼80 km s −1 .…”
Section: The Detection Of H Absorption Against a Radio Lobementioning
confidence: 99%